Evaluation of Melatonin and Antioxidant Levels in the Serum of Breast Cancer Patients - Amjad Mahmood Qadir; Arzu Karatepe; Ayşegül Yazici; Rzgar Farooq Rashid; Pelin Koparir; Rebaz A. Omer; Shamal R. Hama (BioMed Target Journal)
Metabolites and antioxidants can be altered in patients with various diseases, particularly in those with cancer. This study aims to measure melatonin and total antioxidant levels in the serum of breast cancer patients and compare them with a healthy control group. Both groups had serum samples collected at 2:00 a.m. and 9:00 a.m. Melatonin levels were determined using High-performance liquid chromatography (HPLC), while total antioxidant levels were assessed by Enzyme-linked immunosorbent assay (ELISA). Levels of melatonin and total antioxidants differed between the groups. In the control group, the levels of melatonin and total antioxidants were considerably greater compared to the diagnostic group, with a p-value of 0.001. Melatonin and total antioxidant levels were consistently greater at 2:00 than at 9:00. The maximum melatonin levels recorded in the diagnostic and control groups were 39.3 pg/mL and 65.9 pg/mL, respectively. Melatonin levels varied based on the age of the participants, with higher amounts observed in younger participants compared to older people in both groups. The BMI affected the levels of melatonin, with a greater BMI leading to elevated melatonin concentrations. The diagnostic group had a total antioxidant level of 39.3 pg/mL, while the control group had a level of 65.9 pg/mL. The elevated levels of melatonin and total antioxidants in the control group indicate a healthy status. The research demonstrated a significant correlation between melatonin and antioxidant levels in breast cancer patients, with reduced melatonin levels and total antioxidant levels in the diagnosed group. Elevated BMI was linked to reduced melatonin levels.